2009
DOI: 10.4049/jimmunol.0803671
|View full text |Cite
|
Sign up to set email alerts
|

SUMO Conjugation Contributes to Immune Deviation in Nonobese Diabetic Mice by Suppressing c-Maf Transactivation of IL-4

Abstract: It is not clear why the development of protective Th2 cells is poor in type 1 diabetes (T1D). c-Maf transactivates the IL-4 gene promoting Th2 cell development; therefore, abnormalities in c-Maf may contribute to reduced IL-4 production by CD4 cells from nonobese diabetic (NOD) mice. In this study we demonstrate that despite normal expression, c-Maf binds poorly to the IL-4 promoter (IL-4p) in NOD CD4 cells. Immunoblotting demonstrates that c-Maf can be modified at lysine 33 by SUMO-1 (small ubiquitin-like mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
26
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 68 publications
1
26
0
Order By: Relevance
“…MafA and MafB, two large Maf proteins, can be phosphorylated by P38 MAP kinase (Sii-Felice et al, 2005). Sumoylation of c-MAF is proposed to negatively regulate its transcriptional activity, such as mediating IL-4 expression (Leavenworth et al, 2009). MafA was reported to be ubiquitinated (Harmon et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MafA and MafB, two large Maf proteins, can be phosphorylated by P38 MAP kinase (Sii-Felice et al, 2005). Sumoylation of c-MAF is proposed to negatively regulate its transcriptional activity, such as mediating IL-4 expression (Leavenworth et al, 2009). MafA was reported to be ubiquitinated (Harmon et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylation and SUMOylation regulate c-MAF function (Rocques et al, 2007;Leavenworth et al, 2009), whereas ubiquitination leads to c-MAF degradation in the proteasome (Mao et al, 2007). Ubiquitination typically occurs at one or more among various functionally redundant lysine residues in target proteins.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…Post-translational modifications such as SUMOylation, phosphorylation, and ubiquitination are key methods to regulating the biological activity of c-Maf-for example, SUMOylation on c-Maf can negatively modulate its effects on IL-4 transcription, 24,25 whereas phosphorylation increases c-Maf-transforming activity in embryonic mouse cells 26 and enhances IL-4. 27 In MM cells, both c-Maf and MafB can be phosphorylated by the Ser/Thr kinase GSK3, thus increasing MM cell proliferation and colony formation.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have shown that SUMOylation of c-Maf attenuates its IL-4 transcriptional activity (4,5). The transforming activity of MafA, a member of the large Maf family, is dependent on its serine/threonine phosphorylation status (6).…”
mentioning
confidence: 99%